2016
DOI: 10.1002/tox.22304
|View full text |Cite
|
Sign up to set email alerts
|

Di(2-ethylhexyl) phthalate induces apoptosis through mitochondrial pathway in GC-2spd cells

Abstract: Di(2-ethylhexyl) phthalate (DEHP), a plasticizer of synthetic polymers, is a well-known endocrine disrupting chemical (EDC) and reproductive toxicant. Addressing the unclear mechanism of DEHP-induced reproductive dysfunction, this study used GC-2spd cells to investigate the molecular mechanism involved in the DEHP-induced toxicity in the male reproductive system. The results indicated that the apoptotic cell death was significantly induced by DEHP exposure over 100 μM. Furthermore, DEHP treatment could induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…DEHP and MEHP have been demonstrated to possess reproductive toxicity and neurotoxicity, but the toxic mechanisms are still unclear. It has been reported that MEHP can disturb mitochondrial functions, including inhibition of ATP production [ 26 ], reduction of MMP [ 24 , 25 ], and activation of the mitochondria-dependent apoptotic pathways [ 27 , 28 ]. MEHP is also shown to induce ROS-dependent autophagic cell death in human vascular endothelial cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEHP and MEHP have been demonstrated to possess reproductive toxicity and neurotoxicity, but the toxic mechanisms are still unclear. It has been reported that MEHP can disturb mitochondrial functions, including inhibition of ATP production [ 26 ], reduction of MMP [ 24 , 25 ], and activation of the mitochondria-dependent apoptotic pathways [ 27 , 28 ]. MEHP is also shown to induce ROS-dependent autophagic cell death in human vascular endothelial cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…MEHP has been reported to reduce mitochondrial membrane potential (MMP) [ 24 , 25 ] and inhibit the production of ATP [ 26 ]. DEHP and MEHP are also shown to induce mitochondrial apoptosis [ 27 , 28 ]. However, whether MEHP regulates mitophagy, and the contribution of mitophagy to its toxicity have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been shown to induce apoptosis in cells such as mouse Leydig cells (Shen et al, 2019), germ cells (Yang et al, 2019; You et al, 2018b), human granulosa cells (Barbe et al, 2019), and human glioblastoma cells (Zappavigna et al, 2019). Oxidative stress has been reported to play an important role in DEHP-induced apoptosis of GC-2spd cells (Fu et al, 2017). We also found that DEHP induced apoptosis of mouse NE-4C neural stem cells (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, a highly inflammatory milieu rich in TNF- can compromise the intestinal epithelial barrier, further exacerbating inflammatory and apoptotic conditions. In vitro studies have shown that high-molecular-weight phthalates including DEHP alter the expression of genes involved in cell cycle and apoptotic pathways in human leiomyoma cells 29 , ovarian antral follicles 30 , and spermatocytes 29 , 31 . Disruptions in the cell cycle can either lead to abnormal cell proliferation and/or apoptosis, and this may depend on the cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions in the cell cycle can either lead to abnormal cell proliferation and/or apoptosis, and this may depend on the cell type. Although apoptosis and dysregulation of the cell cycle has been observed in the male 31 , 32 and female reproductive tracts 30 , 33 , the impact of DiNP exposure and cell cycle in the colon is unknown.…”
Section: Introductionmentioning
confidence: 99%